The Authority Of Regional Government Of Formation Regional Regulation (Perda) Shari'a - Muhammad Galang Asmara; Gatot Dwi Hendro Wibowo; RR Cahyowati (Faculty of Law, University of Mataram, 2018)
The study, the Authority of regional government Formation of Regional Regulation (Perda) shari'a aims to assess four legal issues, namely: (1) Establish a Regional Authority Perda Syariah; (2) The criteria of Shariah legislation; (3) The procedure of Legislative Shari'ah; (4) Testing Regulation to shariah. This research is normative by using several approaches, namely: (a) Conceptual Approach (Conceptuan aproach); (B) Approaches Legislation (Statute aproach); and (c) Approach the case (Case aproach). The results of this study are expected bermenfaat either for the development of Science and to assist practitioners in the formation of legislation. The research results are as follows: (1) The Regional Authority to establish Sharia legislation can be found in several laws and regulations, both in the Constitution and in the implementation of such rules in the Act; (2) Criteria Sharia legislation is contained in the contents that are based on the values and teachings of Islam; (3) Procedures establishment of sharia in praktinya regulations following the establishment of regulations in general; (4) review of sharia regional regulation also follow the testing procedures and legislation in general. Forward suggest that the process of formation of Perda Syariah scholars to enroll in the area at least in the process of forming draft local regulations. Similarly, in the process of judicial review and evaluation should be based on the sources of Islamic law and involves an element of religious leaders and religious judges.